RESEARCH OF LONG-TERM WAGON-PLATFORM CONSTRUCTIONS ON DENSITY (Transport systems and technologies, 2018)
The article deals with the question of the strength of the main bearing elements of the long-wagon-platform construction, the application of special methods of theoretical and experimental nature. The analysis of frames' elements calculation is performed.
Keywords: long-wagon-platform cars, strength of elements, coefficient of reserve of fa-tigue resistance, design and experimental stresses.